Problem-based learning integrated with flipped classrooms assisted by google sites to improve student mathematics learning achievement - Adam Arya Nugraha; Heni Purwati; Lilik Ariyanto; Sumarti (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
Mathematics is a subject taught at every level of education and has a vital role in everyday life. However, in reality, student mathematics learning achievement tends to be low. One of the reasons is the monotonous learning model or strategy and uninteresting learning media. The learning process is only one-way, making students imitate and record how to answer the questions given by the teacher without understanding the concept correctly. In addition, the learning media used is monotonous and tends to be traditional. Namely, only the whiteboard and several times using an LCD projector, making students bored and passive. So, innovative learning strategies and media are needed to overcome these problems. This study aims to determine the improvement of student mathematics learning achievement in statistics material in grade 10 through implementing Problem-based Learning integrated with Flipped Classroom assisted by Google Sites. The research method used is Classroom Action Research with the Kemmis and McTaggart model, which consists of four stages: Planning, Action, Observation, and Reflection. The results showed increased student mathematics learning achievement in statistics material in grade 10 through implementing Problem-based Learning integrated with Flipped Classroom, assisted by Google Sites. The percentage of classical learning completeness in each cycle is Pre-Cycle 56% with an average of 69.3, Cycle I 72% with an average of 75.7, and Cycle II 89% with an average of 84.7. So, Problem-based Learning integrated with Flipped Classroom, assisted by Google Sites, successfully improves student learning achievement and is recommended to be implemented in the classroom.